Analysis of the Marketing Strategy for Siam Orange (Citrus nobilis) Seedlings at UD Mapan Hortikultura Using SWOT Method - Gautama, Tio Nanda; Kurniawan, Bagus Putu Yudhia (Jurnal Manajemen Agribisnis dan Agroindustri, 2024)
This study was conducted to identify the strengths and weaknesses (internal environment), opportunities and threats (external environment), and to formulate an appropriate marketing strategy for Siam orange seedlings. The SWOT (Strengths, Weaknesses, Opportunities, and Threats) method was used to analyze both internal and external environments, while the QSPM (Quantitative Strategic Planning Matrix) analysis was employed to identify the suitability of management strategies at UD. Mapan Hortikultura. The results of this study can be used to determine the priority of marketing strategies for Siam orange seedlings. This research employs descriptive and exploratory methods, with data collected through interviews and questionnaires. The findings indicate that the company is positioned in Quadrant I of the IE matrix, which represents a growth and build stage. The primary strategies identified in the QSPM are (1) expanding the market reach of the products or adding new markets (score 7.61), (2) utilizing capital and human resources to establish partnerships with closer seed suppliers (score 7.60), and (3) renting a more strategic sales location and optimizing promotion (score 7.55).